2018
DOI: 10.1002/pd.5194
|View full text |Cite
|
Sign up to set email alerts
|

Maternal liver transplant: Another cause of discordant fetal sex determination using cell‐free DNA

Abstract: Noninvasive prenatal testing (NIPT) can very accurately determine fetal sex during pregnancy. We present an exceptional case where NIPT contradicts the ultrasound-based sex determination. The pregnant woman was recipient of a liver transplant from a male donor. Graft-derived cell-free DNA released into the maternal circulation clouded the NIPT-based sex determination. Hence, NIPT is not advisable when the pregnant mother underwent an organ transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 12 publications
(20 reference statements)
0
20
0
Order By: Relevance
“…In our review of the literature, there were four cases where maternal organ transplant was identified as the cause of sex discordance (Table 2) (Balslev-Harder et al, 2017;Bianchi, Parsa, et al, 2015;Neofytou et al, 2018;Wilkins-Haug et al, 2018). In transplant recipients, circulating cell-free DNA found in the plasma, although predominantly hematopoietic in origin, also contains graft-derived DNA from transplanted organs belonging to the donor's genome.…”
Section: Maternal Organ Transplantmentioning
confidence: 99%
See 2 more Smart Citations
“…In our review of the literature, there were four cases where maternal organ transplant was identified as the cause of sex discordance (Table 2) (Balslev-Harder et al, 2017;Bianchi, Parsa, et al, 2015;Neofytou et al, 2018;Wilkins-Haug et al, 2018). In transplant recipients, circulating cell-free DNA found in the plasma, although predominantly hematopoietic in origin, also contains graft-derived DNA from transplanted organs belonging to the donor's genome.…”
Section: Maternal Organ Transplantmentioning
confidence: 99%
“…Significantly increased levels of cell-free DNA (high fetal fraction) are seen when there is evidence of graft rejection, which is accompanied by cellular apoptosis and necrosis. Thus, NIPS for sex chromosome determination is not advisable in patients who have undergone organ or bone marrow transplantation, especially when the donor is male or is of unknown sex (Gregg et al, 2016;Neofytou et al, 2018).…”
Section: Maternal Organ Transplantmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-free DNA (cfDNA) testing for chromosomal aneuploidies offers higher sensitivity and speci city for common autosomal chromosomal aneuploidies and sex determination at an earlier gestational age compared to traditional biochemical and sonographic screening (1). As a result, cfDNA testing is widely selected as the rst choice for detecting common foetal aneuploidies and determining foetal sex (2).…”
Section: Introductionmentioning
confidence: 99%
“…However, the interpretation of the presence of cfDNA poses two major challenges: First, the cfDNA derived from the transplanted organ may be released into the mother's circulation; its level increases when there is tissue damage, and levels of kidneyderived cfDNA are considered an early marker of organ rejection 6. The presence of kidney-derived cfDNA may therefore lead to an incorrect diagnosis of fetal sex or could be a potential cause of discordant (false negative) cfDNA test results7,8 .Second, the performance of cfDNA testing in pregnant women on dialysis is not known. On account of its usual molecular weight, Giorgina B. Piccoli and Elsa Viora contributed equally to the study…”
mentioning
confidence: 99%